The investigation of the potentional comlex from Plantago major to coagulate milk proteins - Grek, Olena; Krasulya, Olena; Chubenko, Larysa; Tymchuk, Alla (My University, 2018)
The ability of proteases and organic acids, that are components of wild plants, to coagulate milk proteins was confirmed. The prospects of this direction in the technology of milk – protein concentrates obtaining was provided. The potential ability of Plantago major leaves to coagulate milk proteins is considered in the article. The mass fraction of dry matters in the juice was within (4.5±0.23). It was found, that the adding of plant coagulant in the amount of 7...9 % from the general amount of milk allows to obtain a clot with such indicators: active acidity – 6.3…6.4 units, moisture mass fraction – 66.00…69.00 %, water – retaining capacity – 60.61...64.26 %. Organoleptic indicators of samples are suitable for consumption. The yield of the protein clot was 184.0...232.7 g from 1000 ml of normalized milk mixture. The state of moisture in herbal – protein clots was established by the method of infrared spectroscopy. The intensive zone of С=О – groups valence oscillations in the area of 1638 cm-1 was observed. This fact indicates about the presence of tightly applied moisture. Microstructural study of clot samples, which where obtained by the use of Plantago major juice showed more developed spatial configuration of gel frame compared with the control sample. It has showed the high structural and mechanical characteristics and therefore water-retaining capacity of the clot. The obtained results are the base for snack cheese products, semi-finished and processed cheeses technology decisions.
Keywords: plantago major leaves’ juice; сік Plantago major; coagulation of milk proteins; коагуляція білків молока; protein –herbal clot; білково-рослинний згусток; кафедра технології молока і молочних продуктів